2003
DOI: 10.1128/mcb.23.8.2800-2820.2003
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplicity of Coactivators Is Required by Gcn4p at Individual Promoters In Vivo

Abstract: Transcriptional activators interact with multisubunit coactivators that modify chromatin structure or recruit the general transcriptional machinery to their target genes. Budding yeast cells respond to amino acid starvation by inducing an activator of amino acid biosynthetic genes, Gcn4p. We conducted a comprehensive analysis of viable mutants affecting known coactivator subunits from the Saccharomyces Genome Deletion Project for defects in activation by Gcn4p in vivo. The results confirm previous findings tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
205
3
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(224 citation statements)
references
References 143 publications
(201 reference statements)
15
205
3
1
Order By: Relevance
“…They were produced by the Saccharomyces Genome Deletion Project from BY4741 (MATa his3⌬1 leu2⌬0 met15⌬0 ura3⌬0) and purchased from Research Genetics͞ Invitrogen (Carlsbad, CA), or they were derived from such strains. All deletion alleles were confirmed by PCR amplification (13). We also confirmed that the arg80⌬ and arg81⌬ strains are defective for arginine-repression of an ARG1-lacZ fusion on plasmid YCp87-ARG1-lacZ (data not shown), and that the arg11⌬ strain is an arginine auxotroph.…”
Section: Methodssupporting
confidence: 61%
See 2 more Smart Citations
“…They were produced by the Saccharomyces Genome Deletion Project from BY4741 (MATa his3⌬1 leu2⌬0 met15⌬0 ura3⌬0) and purchased from Research Genetics͞ Invitrogen (Carlsbad, CA), or they were derived from such strains. All deletion alleles were confirmed by PCR amplification (13). We also confirmed that the arg80⌬ and arg81⌬ strains are defective for arginine-repression of an ARG1-lacZ fusion on plasmid YCp87-ARG1-lacZ (data not shown), and that the arg11⌬ strain is an arginine auxotroph.…”
Section: Methodssupporting
confidence: 61%
“…We also confirmed that the arg80⌬ and arg81⌬ strains are defective for arginine-repression of an ARG1-lacZ fusion on plasmid YCp87-ARG1-lacZ (data not shown), and that the arg11⌬ strain is an arginine auxotroph. Insertion of the coding sequences for 13 myc epitopes at the C termini of ARG80, ARG81, ARG82, and MCM1 was conducted as described (13), and the myc-tagged alleles were verified by PCR amplification and Western analysis of whole-cell extracts (WCEs), using anti-myc antibodies (data not shown). The MCM1-myc strain grew indistinguishably from the parental untagged strain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gcn4 is required for the full induction of .500 genes (Natarajan et al 2001). Four native Gcn4 target genes have been analyzed for their inducibility in a panel of 80 deletion mutants, each of which lacked one of the known coactivators or corepressors of transcription (Swanson et al 2003). Each of the Gcn4 targets displayed a significantly different pattern of dependency, indicating that a different subset of coregulators are recruited by Gcn4 to these promoters.…”
Section: Discussionmentioning
confidence: 99%
“…1). The CCR4-NOT coactivator possesses cytoplasmic mRNA deadenylase activity (Tucker et al 2001), and sequences homologous to the core components of this complex, including homologs of CCR4-which serves as the catalytic subunit (Swanson et al 2003), are present in the parasite (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%